Stem cell status and prognostic applications of cuproptosis-associated lncRNAs in acute myeloid leukemia - Chai, Zhuodong; Yuan, Zhongyue; Chen, Yifei (Frontiers in Cell and Developmental Biology, 2025)
IntroductionAcute myeloid leukemia (AML), a highly heterogeneous hematological malignancy, remains a major challenge in adult oncology. Stem cell research has highlighted the crucial role of long noncoding RNA (lncRNA) in regulating cellular differentiation and self-renewal processes, which are pivotal in AML pathogenesis and therapy resistance.MethodsThis study explores the relationship between cuproptosis-related lncRNAs and AML prognosis, providing novel insights into their impact on hematopoietic stem and progenitor cells.ResultsWe collected clinical information from 214 AML patients in our center and analyzed the association between granulocyte recovery after chemotherapy, cuproptosis, and prognosis. Additionally, we developed a prognostic model—the cuproptosis-associated long noncoding RNA prognostic model (CRLPM)—y analyzing data from The Cancer Genome Atlas (TCGA). Patients were stratified into high- and low-risk groups based on CRLPM, revealing significant survival differences. High-risk patients demonstrated lower sensitivity to chemotherapeutic agents such as Axitinib, GSK429286A, Navitoclax, and ZM-447439, underscoring the need for alternative therapeutic strategies.DiscussionCRLPM offers a promising framework for integrating stem cell-focused approaches into personalized treatment regimens, paving the way for precision medicine in AML management.